TRANSFORMASI BAWASLU DALAM MELAKUKAN PENYIDIKAN TINDAK PIDANA PEMILU - Sofian, Muhamad; Cristian Tampang, Dimas (CENDERAWASIH CONSTITUTIONAL REVIEW, 2025)
The significant increase in electoral criminal offenses across various electoral periods indicates a serious problem within Indonesia’s electoral law enforcement mechanism. Although the Election Supervisory Body (Bawaslu) holds a strong supervisory mandate under Law Number 7 of 2017, its authority in handling electoral crimes remains limited, particularly because investigative functions are fully vested in the Police within the Integrated Law Enforcement Center (Gakkumdu). This condition has resulted in several issues, including weak independence in law enforcement, potential political interference, institutional ego conflicts, and delays in case resolution. This normative legal research examines the urgency of expanding Bawaslu’s investigative authority through an analysis of legislation, legal doctrines, and comparative studies with countries such as France, Brazil, Mexico, and the Philippines. The findings indicate that strengthening Bawaslu’s investigative powers is an urgent necessity to ensure effective, independent, and integrity-based electoral law enforcement. The implications include the need for amendments to electoral regulations, institutional and human resource strengthening within Bawaslu, enhanced accountability and transparency in case handling, and the design of a centralized law enforcement governance system to minimize institutional ego. By granting broader investigative authority, Bawaslu will be able to play an optimal role in safeguarding electoral integrity and strengthening public trust in Indonesia’s democratic processes.